A comparison of the effects of controlled-release levodopa (Madopar CR) with conventional levodopa in late Parkinson's disease. - MacMahon, D G (1990)
In this multicentre study a controlled-release formulation of levodopa and the decarboxylase inhibitor benserazide (Madopar CR) was evaluated in patients with Parkinson's disease exhibiting dose-related fluctuations in motor performance in response to conventional levodopa preparations. The effect of Madopar CR, with or without conventional levodopa/benserazide, on the proportion of time spent "on", "off" or "intermediate" was compared with that of previous conventional levodopa/decarboxylase inhibitor therapy. Evaluation of the two periods of optimum therapy was based on both patient diary data and investigator opinion. Forty seven patients completed the study but full patient diaries were available for only 37. The mean optimum total daily dosage of conventional Madopar was 820 mg taken in a mean of 6.4 doses, compared with a mean optimum daily dosage of combined Madopar CR and conventional Madopar of 1088 mg, taken in a mean of 5.2 doses. Conventional Madopar was taken in addition to Madopar CR in all but eight patients. Madopar CR was felt to be advantageous in 83% and disadvantageous in 11% of patients completing the study. Considering the 37 patients for whom diary data were available, Madopar CR therapy resulted in an increase in the mean time spent "on" (p = 0.016) and a decrease in the mean time spent "off" (p = 0.029) compared with conventional Madopar alone. Individually 25 out of 37 had an increase in "on" time and 19 out of 37 experienced a decrease in "off" time. Thus Madopar CR was found to be beneficial in a significant proportion of patients experiencing fluctuations in response to conventional levodopa.